Upaya Meningkatkan Kemampuan Komunikasi Matematis Siswa Melalui Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Berbantuan Mr Math - Taoefik, Moh (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This classroom action research aims to improve the mathematical communication skills at X grade student of SMA Negeri 2 Narmada Kab. Lombok Barat through cooperative learning type Think Pair Share (TPS) with Mr Math (Microsoft Mathematic). This research was conducted in 2 cycles, with the research subjects were students of class X2 of SMA Negeri 2 Narmada in the academic year 2016/2017 with a total of 24 students. From the research that has been carried out, it is found that the average value of the test of students' mathematical communication skills in the first cycle is 57.58 and the second cycle is 70.05. The percentage of classical completeness in the first cycle was 22.72% and the second cycle was 82.60%. This shows that students' mathematical communication skills have increased. The total average score of students' oral mathematical communication skills in the first cycle was 2.43 with a good enough category and the second cycle was 2.98 with a good category. This shows that students' verbal mathematical communication skills have increased and have reached the specified indicators. The total average score of observations of teaching and learning activities (KBM) in the first cycle was 2.70 with a good category and the second cycle was 3.15 with a good category. Thus, it can be concluded that the Think Pair Share (TPS) type of cooperative learning with Mr.Math can improve students' mathematical communication skills